Leah on the offbeat - Albertalli, Becky (Albertalli, Becky. Simonverse., 2018)
Leah Burke is an anomaly in her friend group: the only child of a young, single mom; her life is decidedly less privileged. She loves to draw but is too self-conscious to show it. And even though her mom knows she's bisexual, she hasn't mustered the courage to tell her friends-- not even her openly gay BFF, Simon. When her rock-solid friend group starts to fracture in unexpected ways, it's hard for Leah to strike the right note. And with prom and college on the horizon, tensions are running high. If only real life was as rhythmic as her drumming...